2009
DOI: 10.1088/0004-637x/703/2/2101
|View full text |Cite
|
Sign up to set email alerts
|

SPECTROSCOPIC EFFECTS IN CH4/H2O ICES

Abstract: Recent observations of CH 4 in different astrophysical objects encourage laboratory research on methane/water ice mixtures. An IR spectroscopy laboratory investigation is presented on these systems. Co-deposited samples are formed by vapor deposition of CH 4 and H 2 O on a cold substrate, in a wide range of stoichiometries, from very diluted mixtures to CH 4 /H 2 O = 2.5 values. Samples are prepared at 14 K and at 40 K, and their temperature behavior is studied when they are warmed up to 60 K. The spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…The n 1 band of methane is a strong feature in Raman spectra, either of the gas phase 31 or from noble gas matrices, 32 and has recently been reported in infrared spectra of CH 4 ice mixtures by Hodyss et al 20 and Ga´lvez et al 19 The observation of this breathing vibration in infrared spectra implies a breakdown of the symmetry of the system, and consequently the formation of a distorted form of CH 4 . The adsorption of CH 4 molecules on water ice surfaces, or the presence of very small methane crystallites distorted from their cubic structure through interactions with the amorphous water environment, could cause such an effect.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The n 1 band of methane is a strong feature in Raman spectra, either of the gas phase 31 or from noble gas matrices, 32 and has recently been reported in infrared spectra of CH 4 ice mixtures by Hodyss et al 20 and Ga´lvez et al 19 The observation of this breathing vibration in infrared spectra implies a breakdown of the symmetry of the system, and consequently the formation of a distorted form of CH 4 . The adsorption of CH 4 molecules on water ice surfaces, or the presence of very small methane crystallites distorted from their cubic structure through interactions with the amorphous water environment, could cause such an effect.…”
Section: Discussionmentioning
confidence: 71%
“…For methane the interaction with water seems weaker, and CH 4 -dist, as we may call this distorted structure, is mainly manifested by the appearance of the forbidden n 1 band. Small shifts or broadenings are also observed on some of the other bands, 19 but they do not allow an independent and simultaneous identification of both methane structures.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Also Quirico & Schmitt (1997) and Gálvez et al (2009) found that CH 4 peaks shift to higher frequencies when highly diluted in N 2 or in H 2 O, respectively. On the other hand, for CH 4 :H 2 O ratios with large methane amount, the opposite behavior was reported, leading to a shift to longer wavelengths (see Figure 3 in Gálvez et al 2009). In the CH 4 :C 2 H 6 mixtures investigated in this work, CH 4 peak positions move to lower frequencies for all dilutions.…”
Section: Comparison Of Spectramentioning
confidence: 98%